Temperature-induced reflectivity changes and activation of hydrogen sensitive optically thin palladium films on silicon oxide - Kalli, Kyriacos; Othonos, Andreas S.; Christofidès, Constantinos (My University, 1998)
The optical properties of several thin metal film palladium-silicon oxide structures are examined at room temperature before and after annealing to 200°C and also at 90°C - in all cases in the presence of hydrogen gas. Multicycling sample activation is shown to occur in the presence of hydrogen at room temperature with an increase in reflectivity on exposure to hydrogen, in contrast to thicker 80 Å films. The reflectivity change increases with increasing film thickness (1-10Å). The surface activation at room temperature, before and after annealing to 200°C, is compared with the performance at 90°C, where it is shown that heat treatment strongly influences the behavior of the metal film.
Keywords: Palladium; Silicon oxide; Temperature; Hydrogen